If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (z + 1) * 2 + 49 = 0 Reorder the terms: (1 + z) * 2 + 49 = 0 Reorder the terms for easier multiplication: 2(1 + z) + 49 = 0 (1 * 2 + z * 2) + 49 = 0 (2 + 2z) + 49 = 0 Reorder the terms: 2 + 49 + 2z = 0 Combine like terms: 2 + 49 = 51 51 + 2z = 0 Solving 51 + 2z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-51' to each side of the equation. 51 + -51 + 2z = 0 + -51 Combine like terms: 51 + -51 = 0 0 + 2z = 0 + -51 2z = 0 + -51 Combine like terms: 0 + -51 = -51 2z = -51 Divide each side by '2'. z = -25.5 Simplifying z = -25.5
| 1.5(2y-4)=3 | | .3(18)+.05x=.15(16+x) | | 13x1/10= | | 15b^2-85b+120=0 | | 3(12t+1)= | | 8(-10)=6(-10)-20-80 | | 5x+34=-2(7x) | | {{0,1/2,1/2},{3/4,0,1/4},{1,0,0}}*{x,y,z} | | 6ln(9x)=24 | | x+3x=2940 | | -11x-y=23 | | 16t^2+32t=1.44 | | 5cos(x)-5cos(2x)=0 | | 0=-4.9t^2+10t+184 | | 16t^2+32t=1.2 | | 3/4x=-30 | | 16t^2+32t=1.9 | | 4(4x+5)=100 | | 16w^2+32t=1 | | 2(x+5)=-10 | | H(t)=-16t^2+87t+199 | | 32+124n=-112n^2+4n | | 4.40x=3.70x+4 | | X=(-X)+8 | | 5z=7a | | 29n-6n=253 | | 12x^2-276x+1080=0 | | x=3(X)+8 | | 1.25x=3.2 | | (7+x)2=206 | | 2a^2-23a+56=0 | | 2x^4-x^3+51x^2-25x+25=0 |